Early comprehensive testing for COVID-19 is essential to protect trauma centers. Issue 4 (October 2020) - Hu, Parker; Jansen, Jan O.; Uhlich, Rindi; Black, Jonathan; Pierce, Virginia; Hwang, James; Northern, David; Stephens, Shannon W.; Lee, Rachael A.; Gelbard, Rondi B.; Holcomb, John B.; Kerby, Jeffrey; et al.
Abstract : BACKGROUND: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic presents a threat to health care systems worldwide. Trauma centers may be uniquely impacted, given the need for rapid invasive interventions in severely injured and the growing incidence of community infection. We discuss the impact that SARS-CoV-2 has had in our trauma center and our steps to limit the potential exposures. METHODS: We performed a retrospective evaluation of the trauma service, from March 16 to 30, following the appearance of SARS-CoV-2 in our state. We recorded the daily number of trauma patients diagnosed with SARS-CoV-2 infection, the presence of clinical symptoms or radiological signs of COVID-19, and the results of verbal symptom screen (for new admissions). The number of trauma activations, admissions, and census, as well as staff exposures and infections, was recorded daily. RESULTS: Over the 14-day evaluation period, we tested 85 trauma patients for SARS-CoV-2 infection, and 21 (25%) were found to be positive. Sixty percent of the patients in the trauma/burn intensive care unit were infected with SARS-CoV-2. Positive verbal screen results, presence of ground glass opacities on admission chest CT, and presence of clinical symptoms were not significantly different in patients with or without SARS-CoV-2 infection ( p > 0.05). Many infected patients were without clinical symptoms (9/21, 43%) or radiological signs on admission (18/21, 86%) of COVID-19. CONCLUSION: Forty-five percent of trauma patients are asymptomatic at the time of SARS-CoV-2 diagnosis. Respiratory symptoms, as well as verbal screening (recent fevers, shortness of breath, cough, international travel, and close contact with known SARS-CoV-2 carriers), are inaccurate in the trauma population. These findings demonstrate the need for comprehensive rapid testing of all trauma patients upon presentation to the trauma bay. LEVEL OF EVIDENCE: Diagnostic tests or criteria, level III, Therapeutic/care management, level IV.